A possible connective tissue primary lymphoepithelioma-like carcinoma (LELC) - Aurilio, G (Cancer Intelligence, 2010)
Lymphoepithelial carcinoma is an undifferentiated nasopharyngeal carcinoma with lymphoid stroma and non-keratinizing squamous cells with distinctive clinical, epidemiological and etiological features. Conversely, lymphoepithelioma-like carcinomas (LELCs) are carcinomas that arise outside the nasopharynx but resemble a lymphoepithelioma histologically. In this case study, LELC presentation in connective tissue (left sternocleidomastoid muscle) is peculiar and unusual, but its diagnosis is supported by histological findings and clinical history, especially long disease free survival and no primary lesions in nasopharynx and lung district. We also discuss the pathogenesis, hypothesizing an embryological theory. To our knowledge, it could be the first reported case of a primary connective tissue LELC to the neck.